Formulation and Evaluation of Ciprofloxacin Hydrochloride Vaginal Tablet and Gel - Akpabio, E. I.; Ofoefule, S. I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Two different dosage forms of ciprofloxacin hydrochloride (CH), namely tablet and gel intended for vaginal drug delivery were formulated. The vaginal tablet was evaluated for weight uniformity, dissolution through an artificial membrane and bioadhesion on pig’s vaginal epithelium. In addition CH vaginal gel was evaluated for pH, consistency and its activity against Escherichia coli and Staphylococcus aureus. The weight, thickness, diameter and hardness of CH vaginal tablets were 0.614 ± 0.20g, 5.53 ± 0.01mm, 12.54 ± 0.02 mm and 1.92 ± 0.20 kgf respectively. There was gradual release of CH from the vaginal tablets through an artificial membrane over ninty minutes. The CH vaginal gel had a pH of 6.67 and consistency of 115.40 ± 0.77 mPa.s. CH vaginal gel was more active against Escherichia coli (MIC = 0.03125 mg/mL) than Staphylococcus aureus (MIC = 0.0625 mg/mL). The release kinetics exhibited by the CH vaginal tablet was zero order (r2 = 0.9032).